NEXUS BETWEEN GOVERNANCE QUALITY, ECONOMIC GROWTH AND POVERTY IN NIGERIA: IMPLICATIONS FOR LONG-TERM DEVELOPMENT GOALS - Aribatise, Adekunle; Olapido, Anthony D.; Adedokun, Daniel (Farabi Journal of Social Sciences, 2026)
Purpose. This study investigates the dynamic relationship between governance quality, economic growth, and poverty reduction in Nigeria over the period 1986–2023. It aims to clarify how governance and macroeconomic performance jointly influence poverty outcomes and to provide empirical evidence relevant to the achievement of long-term development goals, including the Sustainable Development Goals (SDGs). Design/methodology/approach. The study employs annual time-series data from the World Development Indicators (WDI), Worldwide Governance Indicators (WGI), and the World Bank Poverty Database. Key variables include GDP per capita growth, governance quality, investment, infrastructure, and poverty rate. A Vector Error Correction Model (VECM) is applied to examine both short-run dynamics and long-run causal relationships among the variables. Findings. The results indicate that governance quality significantly contributes to economic growth, while economic growth exerts a reducing effect on poverty levels, supporting the Kuznets hypothesis. The error correction term in the poverty equation is negative and statistically significant, confirming the existence of long-run relationships between governance, economic growth, and poverty reduction in Nigeria. Overall, the findings demonstrate that improvements in governance and economic performance are critical drivers of sustainable poverty alleviation. Originality. This study provides an integrated empirical analysis of governance, growth, and poverty within a unified dynamic framework, extending existing literature by capturing both short- and long-term effects in a developing-country context. By combining governance indicators with macroeconomic and poverty data over a long historical period, the research offers novel insights that inform policy debates on institutional reform, infrastructure investment, and inclusive growth strategies in emerging economies. Keywords: Governance quality, Economic growth, Poverty, Kuznets hypothesis, VECM